Knowledge of Pregnant Women about Stunting at the Mesra Midwife Clinic Padangsidimpuan City - Fatimah (International Journal of Public Health Excellence (IJPHE), 2022)
The prevalence of stunting in Indonesia is higher than in other countries, in Southeast Asia, such as Myanmar (35%), Vietnam (23%), Malaysia (17%), Thailand (16%) and Singapore (4%). The purpose of this study was to find out the knowledge of pregnant women about stunting at the Am.Keb intimate midwife clinic in Padangsidimpuan City in 2020. This type of research is descriptive using acedental sampling with 20 respondents. Data collection used a questionnaire sheet, examined based on knowledge, age, education, occupation, parity, and information sources. Based on the results of a study of 20 respondents, the majority lacked knowledge, namely 14 people (70%), based on the age of the majority less, namely 11 people (55%), based on education the majority lacked, namely 8 people (40%), based on work the majority was lacking, namely 10 people (50%), based on parity the majority was lacking, namely 13 people (65%), and based on information sources the majority was lacking, namely 7 people (35%). Based on the research results, it can be concluded that the majority of pregnant women's knowledge about stunting is still lacking, so it is expected that pregnant women will increase their knowledge about stunting through health workers, print media, and electronic media.